PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IV SDN 005 SEDINGINAN - ', Nilawati; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research of background overshadow by lowering of result learn IPS student, with class mean 55,80. this Research form is Research Of Action Class ( PTK) which consist of two cycle which is its execution is started by this Research is executed by 24 March up to 21 April 2016, with subjek amount to 25 student people. This research aim to to mount result learn IPS class student of IV SDN 005 Sedinginan applying of model study of type co-operative of Student Teams Achievement Division ( STAD). this Instrument Research consist of peripheral of and study of instrument data collecting. Technique analyse data the used observation sheet analysis and result learn student. Technique analyse data about activity learn and student relied on observation sheet during execution of action. While data analysis result of learning student show completely result learn student, frequency distribution to span highest value and make-up of result learn student. Pursuant to analysis to activity observation sheet learn and student seen improvement : activity learn cycle of I tired 58,33% cycle of II 87,50%, while student activity cycle of I 62,50%,siklus II 91,67%. Analysis to data result of learning student show improvement among others : complete to learn cycle of I 19 II orang,siklus 25 people, frequency distribution to span highest value to each;every cycle of I equal to 32,69%, cycle of II 40,69%. This matter indicate that applying of model study of type co-operative of STAD can improve result learn IPS class student of IV SD Country 005 Sedinginan. Key Word : Co-Operative Type of Student Teams Achievement Division ( STAD), Result Learn IPS.